(untitled) - Pillay, T. V. R (Oxford, UK, 2005)
'This book covers all aspects of subsistence and commercial aquaculture practised around the world and would be of use to aquaculture students and those involved in the aquaculture industry and fish farms, research institutions, teaching, and aquaculture equipment and feed suppliers
Keywords: Aquaculture,Nuôi trồng thuỷ sản